Characterization and stability monitoring of X-ray focal spots. Issue 1 (2020) - Probst, Gabriel M.; Hou, Qinhan; Boeckmans, Bart; Xiao, YongShun; Dewulf, Wim
Abstract: The characteristics of the X-ray focal spot strongly influence XCT image sharpness and structural resolution. However, current international standards only yield a limited characterization of the focal spot as two perpendicular sizes. Therefore, this paper presents a method for full characterization of the focal spot in terms of both 2D shape and intensity distribution, by applying the inverse Radon transform on a radiograph of a Siemens star. The method is validated through simulations and applied experimentally to two XCT sources. Subsequently, an investigation on how the X-ray tube settings influence focal spot size, shape, intensity and stability is presented.